2015
DOI: 10.1051/0004-6361/201526422
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of the solar network magnetic field around the average supergranule

Abstract: Supergranules in the quiet Sun are outlined by a web-like structure of enhanced magnetic field strength, the so-called magnetic network. We aim to map the magnetic network field around the average supergranule near disk center. We use observations of the line-of-sight component of the magnetic field from the Helioseismic and Magnetic Imager (HMI) onboard the Solar Dynamics Observatory (SDO). The average supergranule is constructed by coaligning and averaging over 3000 individual supergranules. We determine the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 15 publications
4
14
1
Order By: Relevance
“…This ring of higher cork density stands out more clearly than for the observed magnetic field. The observed network field is stronger on the west side of the average supergranule than on the east side, as we detected in our previous study (Langfellner et al 2015a) and as was later also found by Roudier et al (2016). This observation is successfully reproduced by the cork simulation (run #5).…”
Section: Cork Simulationsupporting
confidence: 88%
“…This ring of higher cork density stands out more clearly than for the observed magnetic field. The observed network field is stronger on the west side of the average supergranule than on the east side, as we detected in our previous study (Langfellner et al 2015a) and as was later also found by Roudier et al (2016). This observation is successfully reproduced by the cork simulation (run #5).…”
Section: Cork Simulationsupporting
confidence: 88%
“…This is quite surprising because a detailed check of our data alignment did not show any drift, whereas the NE appears to rotate 6% faster. We observe, as Langfellner et al (2015), a greater presence of the NE in the western part (Fig. 16) of the supergranule.…”
Section: Link Between Horizontal Velocities and Magnetic Elementssupporting
confidence: 70%
“…The length scale (30 Mm) and lifetime (24 to 48 h) promote studies with low resolutions DeRosa & Toomre (2004). Statistical averaging over measurements of numerous supergranules (DeGrave & Jackiewicz 2015;Duvall et al 2014;Langfellner et al 2015) allows us to describe global characteristics, but it is difficult to identify the mechanism of supergranule formation because a correspondence between average quantities and the high temporal and spatial processes is missing.…”
Section: Discussionmentioning
confidence: 99%
“…Here we extent the previous studies on the supergranular brightness excess: How does the convective intensity peak evolve? Does the intensity contrast show an east-west anisotropy, as the magnetic field (Langfellner et al 2015a) or wave travel times (DeGrave & Jackiewicz 2015)? To tackle these questions, we make use of high-quality data from the Helioseismic and Magnetic Imager (HMI) (Schou et al 2012) onboard the SDO spacecraft.…”
Section: Introductionmentioning
confidence: 99%